Response of Mustard Varities to Crop Geometry under Poplar in Terai region of Uttar Pradesh - Mohsin, Faiz; Mohsin, Afreen; Dhaka, S. S. (Indian Forester, 2021)
A field experiment was conducted on effects of crop geometry at farmer’s field in District Pilibhit of Western Terai and Bhabar region of UTTAR PRADESH, India, during 2017- 2019. Three varieties of Mustard, viz; Goldi (V1), Ullahas (V2) and Pant pili sarson-1 (V3) were taken as treatments, four spacings, 40cm Ã— 30cm (S1), 45cm Ã— 20cm (S2), 30cm x 15cm (S3) and 20cm Ã— 10cm (S4), with trees. The experiment was conducted in split plot design with 3-replications and repeated in rabi seasons for two consecutive years. The results revealed that the maximum seed yield was recorded in Pant pili st nd Sarson-1 (1648.0kg/ha and 2052.0kg/ha, respectively in (1st and 2nd year) followed by Goldi and Ullahas. Seed yield of Pant pili sarson-1 was also recorded highest in both the years 2 and 3 years under Poplar plantation (1542.0kg/ha and 1422.0kg/ha, respectively). The same pattern was also observed for stoveryield (kg/ha) in pure as well as in intercropped fields. Plant geometry significantly higher yield was st found in 40cm Ã— 30cm (2241.0kg/ha and 2836.0kg/ha, respectively in 1st and 2nd) in Pant pili Sarson-1. The same pattern was observed in Goldi, followed by Ullahas. Similar results were also noticed in Mustard, grown with trees. Crop geometry (40cm Ã— 30cm), observed the best in respect of number of primary branches/plant and seeds/siliqua, and it was also reflected on seed yield and Stover yield (kg/ha). The Pant pili Sarson-1 - of Mustard is highly suitable and recommended in Terai Region of UTTAR PRADESH due to its higher yield. So, wider spacing is suitable for Pant pili sarson-1; because of their bigger canopy.